Relationship between lifestyle proxies of cognitive reserve and cortical regions in older adults - Šneidere, Kristine; Zdanovskis, Nauris; Mondini, Sara; Stepens, Ainars (Frontiers in Psychology, 2024)
With the rapid increase in the population over 65 years old, research on healthy ageing has become one of the priorities in the research community, looking for a cost-effective method to prevent or delay symptoms of mild cognitive disorder or dementia. Studies indicate that cognitive reserve theory could be beneficial in this regard. The aim of this study was to investigate the potential relationship between lifestyle socio-behavioural proxies of cognitive reserve and cortical regions in adults with no subjective cognitive decline. Overall, 58 participants, aged 65 to 85 years, were included in the data analysis (M = 71.83, SD = 5.02, 20.7% male). Cognitive reserve proxies were measured using the Cognitive Reserve Index questionnaire, while cortical volumes were obtained with the Siemens 1.5T Avanto MRI scanner and further mapped using the Desikan-Killiany-Tourville (DKT) Atlas. Estimated intracranial volume and age were used as covariates. The results indicated that higher occupational complexity was associated with larger cortical volume in the left middle temporal gyrus, the left and right inferior temporal gyrus, and the left inferior parietal lobule, while a combined proxy (the total CRI score) showed a positive relationship with the volume of left middle temporal gyrus and inferior parietal lobule, and pars orbitalis in the right hemisphere. These results might indicate that more complex occupational activities and overall more intellectually and socially active life-style could contribute to better brain health, especially in regions known to be more vulnerable to Alzheimer's disease. This is a provisional file, not the final typeset article functional in their daily lives, pathological ageing involves significant impairment and even disability and with time require professional assistance.Even though pharmacological approaches to the treatment of neurodegenerative diseases, such as Alzheimer's Disease, have been extensively investigated, no definite treatment has been found. Nevertheless, more and more studies indicate the role of cognitive reserve as a means of prolonging the functionally healthy years of older adults (Livingston et al., 2020).